Computer Technologies for Accounting and Reporting for Small and Medium Business in Ukraine: Application Prospects in the Digital Economy Context - YERSHOVAО.; ODNOVOLYK, V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
Rapidly expanding information and communication technologies cause the need in continual software development and modernizations. The modern era of digital economy implies technology integration and emergence of hybrid products and software providing solutions to accounting problems in business sector. The needs of modern business require technological extensions of the accounting software capacities. Most part of research works on computerization of the accounting, pertaining to the previous technological period, has become irrelevant by now. It means that new conditions call for new software. The article’s objective is to investigate the Ukrainian market of software for accounting and reporting for small and medium business in the new technological context. The study is conducted by methods of comparison, analysis, modeling, and experimental use of software samples. Questionings and interviews of enterprises and private entrepreneurs were conducted in time of their consulting on accounting and reporting issues. The software for accounting and reporting is analyzed by principal way of distribution: software acquisition, and SaaS, i. e. software as a service, with examining main advantages and drawbacks of each way. Software products available in Ukraine are broken into three groups by main technology of distribution and main clients for whom they are intended. Characteristics of main representatives from each group are given. Software products are investigated in terms of convenience, functionality and compliance with Ukrainian legal rules. Principal tendencies of software development for small and medium business are shown. Future ways and prospects for software development as a tool of effective business operation are proposed.